Using Cloud Technologies to Develop an Automated Integrated Management System of the Healthcare System in the Conditions of Uzbekistan (Texas Journal of Engineering and Technology, 2025)
The integration of cloud technologies into the healthcare system of Uzbekistan offers significant potential for the development of an automated, efficient, and scalable management system. This paper explores the application of cloud computing in the context of healthcare management, focusing on the benefits it provides in terms of data centralization, real-time access, scalability, and cost-effectiveness. A cloud-based healthcare management system can unify disparate healthcare facilities, streamline administrative processes, and provide seamless access to patient records, leading to improved coordination of care and enhanced patient outcomes.